Reframing Global Engagement - van der Wende, Marijk (International Higher Education, 2017)
Globalization has strongly influenced higher education during the last decades. As in many other sectors, this has generated contradictory outcomes. Higher education has opened up to the world and become more engaged at the global level. But how will this process continue with the current backlash against globalization in Europe and the United States, and what will be the impact of other major geopolitical trends such as the rise of China?